Relationship between obesity indicators and hypertension–diabetes comorbidity among adults: a population study from Central China - Li Li; Ling Li; Ying Wang; Wenwen Wu; Xiaodong Tan; Fen Yang; Jinru Yang; Yifan Wu; Donghan Sun; Ziling Ni; Yaofei Xie (BMJ Open)
Objective To identify the relationship between obesity indicators and hypertension–diabetes comorbidity (HDC) among adults in central China.Design and setting A cross-sectional study was conducted from 1 June 2015 to 30 September 2018 in 11 districts of Hubei Province, China.Participants A total of 29 396 participants aged 18 years or above were enrolled in the study. 2083 subjects with missing data were excluded. Eventually, 25 356 participants were available for the present analysis.Main outcome measures Data were subjected to univariable and multivariable logistic regression to examine the association between obesity indicators (body mass index (BMI), waist circumference (WC) and waist-to-height ratio (WHtR)) and HDC prevalence. Crude odds ratio and adjusted OR (AOR) with associated 95% CI were calculated.Results Overall, 2.8% of the respondents had HDC. The odds of HDC prevalence increased with the BMI of the participants (18.5≤BMI (kg/m2)≤23.9—1; 24≤BMI (kg/m2)≤26.9—AOR: 5.66, 95% CI: 4.25 to 7.55; BMI (kg/m2)≥27—AOR: 7.96, 95% CI: 5.83 to 10.87). The risk of HDC also increased with the WHtR of participants (WHtR≤P25—1; P25≤WHtR≤P50—AOR: 1.73, 95% CI: 1.10 to 2.71; P50 ≤WHtR≤P75—AOR: 2.51, 95% CI: 1.60 to 3.92; WHtR≥P75—AOR: 3.22, 95% CI: 2.01 to 5.16). Stratified analysis by gender showed that high BMI and WHtR were risk factors of HDC in males and females. However, the odds of HDC prevalence increased only when WHtR≥P75 in males, whereas the probability of HDC increased when WHtR≥ P25 in females.Conclusion High BMI and WHtR can increase the risk of HDC among Chinese adults. Reasonable control of BMI and WHtR may be beneficial in preventing HDC. Females should focus on maintaining an optimal WHtR earlier.